Finite element computational development for thermo-mechanical analysis of plane steel structures exposed to fire - Neves,Natan Sian das (2022)
Abstract This article presents a numerical formulation based on finite element procedures for application in nonlinear thermo-mechanical analyses of steel planar structures under fire condition. The mechanical properties of structural elements degrade when subjected to high temperatures, resulting in significant reductions in strength and stiffness. Under these conditions, the structures present complex behaviors associated with nonlinear models, requiring an advanced mathematical analysis. As such, a computer program called NASEN has been developed to investigate the behavior of steel structures subjected to fire, considering the effects of geometric and material nonlinearity, as well as the thermal gradients acting on the cross-section. The solution strategy is based on sequential coupling of numerical processes. Initially, the two-dimensional thermal field is determined, followed by an assessment of structural behavior. In each solution step, corrective processes are implemented to ensure convergence of the temperature and displacement nodal vectors. Numerical experiments are performed in order to evaluate the accuracy and capacity of the computer program. Results are compared with experimental tests and computer simulations found in pertinent literature. The program shows good agreement with reference solutions, indicating its accuracy and applicability for the cases studied.